Methyl 2-(2-amino-1,3-thiazol-4-yl)-2-[(Z)-methoxycarbonylmethoxyimino]ethanoate - Shahzad Sharif; M. Nawaz Tahir; Islam Ullah Khan; Sarfraz Ahmad; Manan Ayub Salariya (Acta Crystallographica Section E, 2009)
In the molecule of the title compound, C9H11N3O5S, the thiazole ring is oriented at dihedral angles of 87.33 (3) and 87.18 (3)° with respect to the planar (r.m.s. deviations 0.0136 and 0.0139 Å) methyl ester groups. The dihedral angle between the methyl ester groups is 44.20 (3)°. In the crystal structure, intermolecular N—H...N, N—H...O and C—H...O hydrogen bonds link the molecules along the a axis, through R22(8) and R22(22) ring motifs, forming infinite two-dimensional polymeric sheets. π–π Contacts between the thiazole rings [centroid–centroid distance = 3.536 (2) Å] may further stabilize the structure.